Competitive adsorption of heavy metal ions (Pb2+, Cu2+, and Ni2+) onto date seed biochar: batch and fixed bed experiments. Issue 6 (13th April 2019) - Mahdi, Zainab; Yu, Qiming Jimmy; El Hanandeh, Ali
ABSTRACT: In a multicomponent systems, the adsorption of Pb 2+, Cu 2+, and Ni 2+ by date seed biochar exhibited competitive behavior. Compared to single component systems, the adsorption capacities of each ion were reduced by 48–75% in both batch and column experiments. Surface complexation with carboxyl and hydroxyl functional groups played a major role in the removal mechanism. Ion exchange mechanism accounted for 37–40% of the total adsorption compared to 57–72% in single component systems. Modified Langmuir isotherm best described the systems. Adsorption capacities and selectivity follow the order: Pb 2+ > Cu 2+ > Ni 2+ . Multi-stage sequences system is recommended to avoid premature exhaustion of biochar.